The Civilization of Sandur Watch’s Transcendence in the Age of Globalization - Hidajad, Arif; Zulaeha, Ida; Sahid, Nur; Cahyono, Agus (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
This research departs from the background that Sandur has a form of sublimation of transcendent normativity values conveyed through folk theater products. The main focus of the problem’s formulation in this study is to analyze the symbol system in Sandur, which is to connect to the meaning of transcendence normativity to be associated with the area of civilized society in the era of globalization. The aim is to prove the existence of the normative meaning of transcendence from the symbol system of Sandur’s spectacle and to implement the meaning of the normativity of the transcendence of Sandur as an effort to civilize society to face the negativity of globalization. The analysis in this study was carried out using descriptive qualitative methods through observation, interviews, documentation, and literature, then described based on the concept of Clifford Geertz’s interpretive anthropology. The results obtained in this study are (1) the symbol system in Sandur’s rituals, scenes, and songs has a transcendent normativity in the form of Mutmainah’s attitude and Beyond meaning, as a network of interactions and relationships in the vertical and horizontal dimensions, and (2) the transcendence civilization of Sandur’s spectacle in the era of globalization through Beyond meanings and attitudes Mutmainah to face the negative culture of globalization that allows the occurrence of cultural and moral decadence. The problem that becomes the focus of the transcendence civilization of Sandur’s spectacle in this study is not rejecting the achievement of globalization progress but rather an attempt to internalize the values in the sign of globalization to maintain the mentality of cultural ecstasy of the people born of transcendence normativity.